Sailing over frozen Windy Arm, Tagish Lake, Yukon Territory, 1898. - Curtis, Asahel, 1874-1941 (1898)
Men with sail attached to sled and dog team traveling across frozen lake. Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number